2011
DOI: 10.1099/ijs.0.023556-0
|View full text |Cite
|
Sign up to set email alerts
|

Parasutterella secunda sp. nov., isolated from human faeces and proposal of Sutterellaceae fam. nov. in the order Burkholderiales

Abstract: A novel, strictly anaerobic, non-spore-forming, Gram-reaction-negative coccobacillus bacterium, designated strain YIT 12071 T , was isolated from human faeces. Biochemically, this strain was largely unreactive and asaccharolytic. Growth of this strain in peptone-yeast-extract broth was weak, producing no visible turbidity, and no short-chain fatty acids were detected as an end product of metabolism. Following 16S rRNA gene sequence analysis, strain YIT 12071 T was found to be most closely related to Parasutter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…A more detailed analysis of the changes in the microbial community structure showed that individual A exhibited a significant increase in Sutterellaceae and Acidaminococcaceae (0.44 → 15.34%) in the protein-rich medium after 48 hr of treatment (Table 1) that was not observed for individual B (Table 1). Both bacterial families are known to be commensal of the human gut (D'Auria et al, 2011;Morotomi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A more detailed analysis of the changes in the microbial community structure showed that individual A exhibited a significant increase in Sutterellaceae and Acidaminococcaceae (0.44 → 15.34%) in the protein-rich medium after 48 hr of treatment (Table 1) that was not observed for individual B (Table 1). Both bacterial families are known to be commensal of the human gut (D'Auria et al, 2011;Morotomi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Sutterellaceae and Rikenellaceae are both increased in diabetic mice. Sutterellaceae are Gram negative, oxidase-and catalase-negative bacteria that grow under microaerophilic or anaerobic conditions (44), belonging to the phylum Proteobacteria. Proteobacteria is a major phylum of Gram-negative bacteria, including a wide variety of pathogens, such as Escherichia, Salmonella, Helicobacter, Yersinia, etc.…”
Section: Bacterial Taxonomic Differences At Family Levelsmentioning
confidence: 99%
“…Among the other bacterial groups significantly impacted by the lipoprotein emulsion structure, Sutterella and Parasutterella proportions significantly increased under the GCE diet. Both genera contain bile acids resistant species . We previously proposed that lipids in GCE diet are less digestible .…”
Section: Discussionmentioning
confidence: 99%
“…Both genera contain bile acids resistant species. [54,55] We previously proposed that lipids in GCE diet are less digestible. [23,24] They may require longer exposure to bile acids in the digestive system for complete absorption.…”
Section: Chronic Effects Of the Emulsion Structure In The Distal Regimentioning
confidence: 99%